2009
DOI: 10.1164/rccm.200809-1436oc
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 17q21 Gene Variants Are Associated with Asthma and Exacerbations but Not Atopy in Early Childhood

Abstract: Variation at the chromosome 17q12-q21 locus was associated with approximately twofold increased risk of recurrent wheeze, asthma, asthma exacerbations, and bronchial hyperresponsiveness from early infancy to school age but without conferring risk of eczema, rhinitis, or allergic sensitization. These longitudinal clinical data show this locus to be an important genetic determinant of nonatopic asthma in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
164
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(182 citation statements)
references
References 40 publications
16
164
2
Order By: Relevance
“…Analyses by the GABRIEL consortium revealed no association between the ORMDL3/GSDMB locus and IgE levels, a commonly used indicator for atopy (11). This has been replicated in numerous studies (8,9,13,18,22,23). The absence of any overlap between the most highly associated asthma-susceptible SNPs and serum IgE at any locus tested suggests separate, genetically distinct pathways.…”
Section: Association Of the 17q21 Locus With Asthma Typesmentioning
confidence: 79%
“…Analyses by the GABRIEL consortium revealed no association between the ORMDL3/GSDMB locus and IgE levels, a commonly used indicator for atopy (11). This has been replicated in numerous studies (8,9,13,18,22,23). The absence of any overlap between the most highly associated asthma-susceptible SNPs and serum IgE at any locus tested suggests separate, genetically distinct pathways.…”
Section: Association Of the 17q21 Locus With Asthma Typesmentioning
confidence: 79%
“…6 rs7216389 is located in an intron of the GSDMB gene (encoding the gasdermin-like protein), but its association with asthma was originally linked to the expression of the nearby ORMDL3 gene (encoding the ORM1-like 3 protein). Subsequent reports have provided further support for the association of this 17q21 locus with childhood [7][8][9][10][11] and persistent asthma, 12 but the mechanisms underlying this effect remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There is emerging evidence that the innate immune response in asthma is impaired, airway inflammation may modulate the response to triggers and genetic polymorphisms may confer an increased risk of exacerbations [24]. Because it has been already suggested that the presence of eosinophilic inflammation in the bronchial wall promotes the development of an exacerbation in combination with a viral infection, a clinical research study concerning the eosinophil response in the bronchial wall to S. commune or to the secretory products of this fungus will also be important to elucidate the mechanisms underlying the exacerbation of asthma in the future.…”
Section: Discussionmentioning
confidence: 99%